Pendidikan Kewirausahaan dan Efikasi Diri Serta Pengaruhnya Terhadap Intensi Berwirausaha - Didit Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Students are potential sources that act as economic builders of a nation. In the future, they become the basic foundation of the nation to develop, one of which is through the development of the economy. They are expected not only to become job seekers but to become job providers. This is shown through learning entrepreneurship courses. The course provides an overview of how an entrepreneur is formed along with its challenges. This study aims to examine the effect of entrepreneurship education and self-efficacy on entrepreneurial intentions. The study was conducted in four private universities in the cities of Surabaya and Mojokerto involving 150 respondents from among students. The analytical tool used is the Structural Equation Model. Based on the results of hypothesis testing, it shows all positively significant effects. Entrepreneurship education has a positive effect on entrepreneurial intentions. Entrepreneurship education has a positive and significant influence on self-efficacy. Self-efficacy has a positive and significant influence on entrepreneurial intentions